Inside Back Cover: Wafer‐Scale Oxygen‐Doped MoS2 Monolayer (Small Methods 6/2021). Issue 6 (10th June 2021) - Wei, Zheng; Tang, Jian; Li, Xuanyi; Chi, Zhen; Wang, Yu; Wang, Qinqin; Han, Bo; Li, Na; Huang, Biying; Li, Jiawei; Yu, Hua; Yuan, Jiahao; et al.
Abstract : In article number 2100091, Yang, Zhang, and co‐workers realize in situ substitutional oxygen doping of 2‐inch wafer‐scale monolayer MoS2 through chemical vapor deposition. The doped films (MoS2‐ x O x ) are uniform with tunable doping levels and their bandgaps decrease with the increased oxygen concentrations. Wafer‐scale monolayer MoS2‐ x O x films hold promise on the practical applications for high‐performance large‐scale 2D electronic devices.